2000
DOI: 10.1523/jneurosci.20-02-00878.2000
|View full text |Cite
|
Sign up to set email alerts
|

Neural Systems Underlying the Recognition of Familiar and Newly Learned Faces

Abstract: Memory for famous faces can be used to examine the neural systems underlying retrieval from long-term memory. To date, there have been a limited number of functional neuroimaging investigations examining famous face recognition. In this study, we compared recognition of famous faces to recognition of newly learned faces. Whole-brain, event-related functional magnetic resonance imaging was used to image regional changes in neural activity in 11 subjects during the encoding of unfamiliar faces and during familia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
276
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(319 citation statements)
references
References 49 publications
41
276
0
2
Order By: Relevance
“…As in the previous study (5,16), no major hemispheric predominance seemed to be effective for the EP components. That a multitude of brain regions participated in face processing was supported by a recent fMRI study (14).…”
Section: Category-related Processing: Faces Versus Nonface Stimulimentioning
confidence: 83%
See 1 more Smart Citation
“…As in the previous study (5,16), no major hemispheric predominance seemed to be effective for the EP components. That a multitude of brain regions participated in face processing was supported by a recent fMRI study (14).…”
Section: Category-related Processing: Faces Versus Nonface Stimulimentioning
confidence: 83%
“…However, while these studies demonstrated relevant time epochs, the localization of these processes needs to be done using complementary techniques. Thus, over the last 10 to 20 years, positron emission tomography (PET) and functional MRI studies looked further into the anatomical correlates in vivo (12)(13)(14). While the underlying brain structures can now be precisely localized to within a precision of a few millimeters, no information about the temporal aspects of face processing was obtained using these techniques.…”
mentioning
confidence: 99%
“…The sources for the components with latencies of about 400 ms in face/word tasks have been located by other authors to be in the temporal and frontal cortices (Halgren et al, 1994a,b). Wide, mostly temporal, networks are implicated in the metabolic studies as sources for personal identity-related brain activity (Haxby et al, 2000;Leveroni et al, 2000;Tempini et al, 1998). It is possible that our temporal sources (dipoles 3 and 4) reflect such activity, at least partially.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the PCC activation is also elicited during recognition of visual and auditory materials drawn from a person's daily life. When individuals are presented with names of friends and family (Maddock, Garrett, & Buonocore, 2001), faces and voices of friends and family (Shah et al, 2001), famous faces (Leveroni et al, 2000), personal belongings (Leveroni et al, 2000;Sugiura, Shah, Zilles, & Fink, 2005), familiar places (Sugiura et al, 2005), and personal life events (Addis, Moscovitch, Crawley, & McAndrews, 2004;Levine et al, 2004), PCC activation is more pronounced than when viewing similarly constructed, but novel materials.…”
Section: Introductionmentioning
confidence: 99%